The (pro-)cyclicality of government consumption in the EU and official expectations of future output growth: New evidence - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2020)
Data from member states' Stability and Convergence Programmes from 2011 to 2018 are used to assess the cyclicality of government consumption in the EU after the European Semester took effect. Econometric estimations, which address endogeneity issues, find the intended (ex-ante) fiscal policy to be pro-cyclical in nature. Government consumption is also found to be pro-cyclical ex-post but to a much lesser extent than ex-ante. This appears to be largely owing to a forecasting bias on the part of official forecasters occurring, despite the purported improvements to EU member states' surveillance and forecasting mechanisms that have been put in place in recent years to address such bias.
Keywords: C23; E62; H68; 330; Cyclicality of fiscal policy; forecasting bias; European Semester